Geology, geochronology and geochemistry of the Saishitang Cu deposit in the East Kunlun Orogenic Belt, NW China. Issue 6 (28th February 2022) - Ma, Xiaoping; Zhao, Yun; Xue, Chunji; Wang, Xiongfei; Chen, Jia; Yan, Yu; Li, Xuguang; Qiu, Mingfeng
Abstract : The Saishitang deposit, located in the eastern part of the Eastern Kunlun Orogenic Belt, NW China, hosts important Cu mineralization. The ore occurs as stratiform bodies in Lower–Middle Triassic siltstone and siliceous rock and as lenticular bodies at the contacts between quartz diorite and marble. The whole‐rock geochemistry and Si–O isotopic compositions of the siliceous rocks suggest a sedimentary origin. The quartz diorite has a weighted mean zircon U–Pb age of 215.5 ± 0.9 Ma. The quartz diorite exhibits high SiO2 (63.91–69.48 wt%), Al2 O3 (14.98–17.11 wt%) and Na2 O (2.17–4.58 wt%) contents, with A/CNK values of 0.79–1.10, similar to those of calc‐alkaline I‐type granites. The quartz diorite exhibits weak negative Eu anomalies (δEu = 0.80–0.99), enrichment in light rare earth elements, Rb, Ba, K and Pb and depletion in heavy rare earth elements, Nb, Ta, P and Ti. The Pb isotopic compositions suggest that the skarn ore, quartz diorite and host rocks are closely correlated, reflecting a common source. By contrast, the Pb isotopic compositions of sulphide ores hosted within siltstone are heterogeneous, suggesting multiple lower‐crustal and upper‐mantle sources. By integrating our geological and geochemical data, we propose that the Saishitang deposit was formed by exhalative sedimentary mineralization in a back‐arc basin and overprinted by Indosinian skarn mineralization in a post‐collision extensional environment. Abstract : The Saishitang deposit experienced exhalative sedimentary mineralization in a back‐arc basin and was overprinted by Indosinian skarn mineralization in a post‐collision extensional environment.